Development of Literacy Questions Based on Hots Using Context Covid-19 - Puspitasari, Linda; Alwi, Zahra; Suhardi, Suhardi; Zulkardi, Zulkardi (Journal of Education Research and Evaluation, 2021)
In 2021, the National Examination (UN) will be replaced with Minimum Competency Assessment and Character Survey. This paper will present how HOTS-based literacy questions as a substitute for UN questions. The research involved seventh-grade teachers and students of SMP Negeri 1 Semende Darat Laut. The following results were obtained.Â  HOTS-based literacy questions contain items that measure higher-order thinking competencies. It is in line with educational goals to develop higher-order thinking skills and other competencies that are more relevant to the 21st Century. HOTS-based literacy reasoning questions in line with these procedures, and in line with the Program for International Student standards Assessment (PISA). This needs to be done considering the PISA score of students from Indonesia is always low. It was also explained from the same source that by getting students used to working on PISA type questions it would improve students' higher-order thinking skills.